E-Cigarette Usage and Arthritis in the United States, a Nationwide Cross-Sectional Survey - Tian, Yi; Jiao, Zhihua; Mao, Yingying; Zhang, Zhenyu (Frontiers in Pharmacology, 2022)
Aim: The prevalence of the use of electronic cigarettes (e-cigarettes) has grown rapidly in the past decade in the United States. While numerous studies have demonstrated combustible cigarette is closely associated with an increased risk of arthritic disease, little is known about the effect of e-cigarette usage on arthritis. We aimed to determinate if e-cigarette usage is associated with an increased risk of arthritis. Methods: Data were obtained from the Behavioral Risk Factor Surveillance System, which is the largest national telephone-based survey of randomly sampled adults in the United States. A total of 924,882 participants with information on e-cigarette usage and arthritis were included. We used multivariable logistic regression to estimate the risk of arthritis associated with e-cigarette usage. Results: Of the 924,882 participants, there were 30,569 (3.3%) current e-cigarette users, and 314,190 (25.9%) reported to have arthritis diseases. In the fully adjusted model, we observed that the odds ratio (OR) (95% confidence interval) of arthritis diseases was 1.81 (95% CI, 1.70-1.93) for current e-cigarette users compared with never e-cigarette users. The ORs of arthritis were 1.31 (95% CI, 1.18-1.47), and 1.55 (95% CI, 1.42-1.69) among sole e-cigarette and dual users compared with never e-cigarette users, respectively. Conclusions: This is the first study to observe a cross-sectional association between e-cigarette usage and arthritis, and the findings were consistent in both sole-e-cigarette users and dual users. Our findings provide evidence that e-cigarette usage might be an important risk factor for arthritis diseases, which may have regulatory implications for e-cigarette control.